Podbevškova pesniška šola, Trije labodje in zaton "bombaša" - Dović, Marijan (Slavistična revija, 2020)
This article examines the role of the so-called Novo Mesto Spring movement, particularly the role of the poet Anton Podbevšek, on the dynamics of Slovenian avant-garde art in the first decade after the World War I. It outlines Podbevšek's controversial rise to celebrity status soon after his arrival in Ljubljana in 1920, his extraordinary influence on contemporary young poets, reflected in the literary contributions to the first issue of the magazine Trije labodje (The Three Swans, 1922), and, finally, analyzes Podbevšek's irrevocable decline after 1925. Podbevšek's (self)destructive behavior in this period proves to be among the important reasons why the attempt to consolidate Slovenian historical avant-garde art, which might have taken place around The Three Swans, failed.
Keywords: Jarc, Miran; Kogoj, Marij; labodovci; Novo mesto Spring; novomeška pomlad; Podbevšek, Anton; Slovenian interwar avant-garde; Slovenian literature; slovenska književnost; slovenska zgodovinska avantgarda; The three swans; Trije labodje; Vidmar, Josip